Leaving Gangs and Desisting From Crime Using a Multidisciplinary Team Approach: A Randomized Control Trial Evaluation of the Gang Reduction Initiative of Denver (GRID), Colorado, 2014-2022 - Pyrooz, David C. ([Verlag nicht ermittelbar], 2024)
This dataset is from an evaluation of an intervention program designed to facilitate disengagement from gangs and desistance from crime. Led by the Gang Reduction Initiative of Denver (GRID), a multidisciplinary team and street outreach workers carried out the randomized controlled trial between 2019 and 2022. One hundred forty-three people referred to GRID were assigned at random to receive individualized, coordinated case management, developed by the multidisciplinary team and facilitated by street outreach workers. Intake data was gathered for each referred individual by the referring agent (i.e. their probation officer) and sent to the study personnel. A baseline survey was attempted for each individual shortly after referral; a follow-up survey was attempted roughly 10 months after referral. Judicial data for each referred individual was gathered from official sources from the 5 years prior to referral and for an 18-month period after referral.